Saving America? : Faith-Based Services and the Future of Civil Society - Wuthnow, Robert (Book collections on Project MUSE., 2006)
On January 29, 2001, President George W. Bush signed an executive order creating the White House Office of Faith-Based and Community Initiatives. This action marked a key step toward institutionalizing an idea that emerged in the mid-1990s under the Clinton administration--the transfer of some social programs from government control to religious organizations. However, despite an increasingly vocal, ideologically charged national debate--a debate centered on such questions as: What are these organizations doing? How well are they doing it? Should they be supported with tax dollars?--solid answ.